The "central vein sign" in patients with diagnostic "red flags" for multiple sclerosis: A prospective multicenter 3T study. (April 2020) - Maggi, Pietro; Absinta, Martina; Sati, Pascal; Perrotta, Gaetano; Massacesi, Luca; Dachy, Bernard; Pot, Caroline; Meuli, Reto; Reich, Daniel S; Filippi, Massimo; Pasquier, Renaud Du; Théaudin, Marie
Background: The central vein sign (CVS) has been shown to help in the differential diagnosis of multiple sclerosis (MS), but most prior studies are retrospective. Objectives: To prospectively assess the diagnostic predictive value of the CVS in diagnostically difficult cases. Methods: In this prospective multicenter study, 51 patients with suspected MS who had clinical, imaging, or laboratory "red flags" (i.e. features atypical for MS) underwent 3T fluid-attenuated inversion recovery (FLAIR*) magnetic resonance imaging (MRI) for CVS assessment. After the diagnostic work-up, expert clinicians blinded to the results of the CVS assessment came to a clinical diagnosis. The value of the CVS to prospectively predict an MS diagnosis was assessed. Results: Of the 39 patients who received a clinical diagnosis by the end of the study, 27 had MS and 12 received a non-MS diagnosis that included systemic lupus erythematosus, sarcoidosis, migraine, Sjögren disease, SPG4-spastic-paraparesis, neuromyelitis optica, and Susac syndrome. The percentage of perivenular lesions was higher in MS (median = 86%) compared to non-MS (median = 21%; p  < 0.0001) patients. A 40% perivenular lesion cutoff was associated with 97% accuracy and a 96% positive/100% negative predictive value. Conclusion: The CVS detected on 3T FLAIR* images can accurately predict an MS diagnosis in patients suspected to have MS, but with atypical clinical, laboratory, and imaging features.